Public Transport in the Federal Capital Territory, Abuja: A GIS-Based Analysis of Key Indicators - Pillah, Tyodzer Patrick (INTERNATIONAL JOURNAL OF CAPACITY BUILDING IN EDUCATION AND MANAGEMENT, 2024)
Transport policymakers and planners are worried about the detrimental effects on the physical and socioeconomic surroundings caused by the high number of private cars used for commuting in the Federal Capital Territory (FCT), Abuja. Public transportation pricing, service frequency, walking distance to access points, and waiting time at terminals/bus stops are the four critical variables that this study uses to analyze commuters' access to public transportation. Locations with similar average values for waiting time, transportation fare, bus service frequency, and distance to public transportation access points were identified through data analysis and manipulation in the Geographic Information System (GIS) Arc-GIS 9.3 environment. Commuters and public transportation operators were surveyed and interviewed using a mix of questionnaires and GPS devices (Garmin 62x). The Gwagwalada and Zuba axis had the best public transport access in FCT, with 58 mean bus frequencies per day, an average of 109 meters to access points, a mean waiting time of about 20 minutes in the park, and a mean transport fare per tip of N158. However, it still did not meet best practices. The study's recommendations include making public transportation routes, stops, and terminals more streamlined to match the FCT's present pattern of physical growth and urging relevant parties to increase their efforts to make public transportation accessible and inexpensive.